Synthesis of novel series of 3, 5-disubstituted imidazo[1, 2-d] [1, 2, 4]thiadiazoles involving SNAr and Suzuki–Miyaura cross-coupling reactions. Issue 10 (23rd February 2022) - Pescheteau, Clémentine; Place, Matthieu; Sava, Alexandru; Nunes, Lea; Profire, Lenuta; Routier, Sylvain; Buron, Frédéric
Abstract : A convenient design of 3, 5-disubstituted imidazo[1, 2- d ][1, 2, 4]thiadiazoles is reported from 2-mercaptoimidazole, which afforded a versatile platform that was then used to access a variety of original heterocycles. Abstract : The first access to 3, 5-disubstituted imidazo[1, 2- d ][1, 2, 4]thiadiazole derivatives is reported. The series were generated from 2-mercaptoimidazole, which afforded the key intermediate bearing two functional positions. The SN Ar reactivity toward tosyl release at the C-3 position was investigated and a regioselective electrophilic iodination in C-5 position was performed to allow a novel C–C bond using Suzuki–Miyaura reaction. Palladium-catalyzed cross-coupling conditions were optimized. A representative library of various boronic acids was employed to establish the scope and limitations of the method. To complete this methodological study, the influence of the nature of the C-3 imidazo[1, 2- d ][1, 2, 4]thiadiazole substitutions on the arylation in C-5 was investigated.